Features and function of women's language in nino's utterances on Ali and Nino ( 2016 ) movie - Amartya Suci Kussafa Anandini (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
wt,1/ yna, c.1